Partisipasi Masyarakat Dalam Pembangunan Di Desa Kuala Sempang Kecamatan Seri Kuala Lobam Kabupaten Bintan Tahun 2014 - kustiawan, kustiawan; sofi, kohen (Kemudi, 2017)
By paying attention to the experience of regional autonomy in the past that embraces the principle of real autonomy and responsible with an emphasis on more autonomy is the obligation of the right, then in this law granting autonomy to local authority districts and areas of the city based on the principles of decentralization alone in the form of broad autonomy, real and responsible. With the implementation of the research in the village of Kuala Sempang District of Kuala Lobam Series Bintan regency is expected to provide an overview of how the process of public participation in the implementation of regional development so that the concept of participatory development that has been applied can be dosed and can be used as a reference in subsequent studies related to substances.From the research that has been carried out, can be drawn that the application of community participation in development in the village of Kuala Sempang District of Kuala Lobam Series Bintan regency. If the view of the indicators of community participation in the development of community participation in the form of an idea or ideas, participation in the form of materials, participation in the form of labor and community participation in the form of utilization of development. The contribution of participation in the form of energy is the largest in any development process implemented. Participation in the form of utilization of development for the community is when development is aimed at the welfare of rural communities, the people will really take advantage and menajaga development that has been implemented by the village government to the people in the village of Kuala Sempang. Although in the process encountered a small obstacles but does not reduce the spirit of mutual aid societies to build their village.